2001
DOI: 10.1111/j.1478-4408.2001.tb00088.x
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between the solubility of disperse dyes and the equilibrium dye adsorption in supercritical fluid dyeing

Abstract: In order to understand the dyeing behaviour of synthetic fibres in supercritical carbon dioxide, the solubility of some disperse dyes in supercritical fluid, as well as the rate of dyeing and the equilibrium adsorption of these dyes, have been studied. Dye solubility was measured by a dynamic analytic method at a range of pressure (7.5–25 MPa) and temperature (50–145 °C). The apparent rate of dyeing was measured and the dyeing isotherm was obtained by plotting the equilibrium dye adsorption against the equilib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
0
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 23 publications
1
33
0
1
Order By: Relevance
“…It has been reported that the conventional dyeing time for PET fiber in scCO 2 is 30-120 min. 11,12 With regard to the swelling of PET fiber in CO 2 , Hirogaki et al 24 have described that the swelling behavior reached a maximum after 2 h. Therewith, a time period of 2 h was adopted here to impregnate the PET fabric with cross-linking agents in scCO 2 . Figure 3 shows the influence of pressure on the uptake of the cross-linking agent by the fabric at the three temperatures.…”
Section: Supercritical Treatment Of Pet Fabricmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that the conventional dyeing time for PET fiber in scCO 2 is 30-120 min. 11,12 With regard to the swelling of PET fiber in CO 2 , Hirogaki et al 24 have described that the swelling behavior reached a maximum after 2 h. Therewith, a time period of 2 h was adopted here to impregnate the PET fabric with cross-linking agents in scCO 2 . Figure 3 shows the influence of pressure on the uptake of the cross-linking agent by the fabric at the three temperatures.…”
Section: Supercritical Treatment Of Pet Fabricmentioning
confidence: 99%
“…Recently, the use of scCO 2 fluid in polymer processing has had a marked effect on dyeing, [11][12][13] expanding foam, 14 plating, 15 impregnation, [16][17][18] etc. ScCO 2 (Tc ¼ 31 C, Pc ¼ 73.8 bar) is one of the most commonly used supercritical fluids.…”
Section: Introductionmentioning
confidence: 99%
“…As a consequence in the last few decades, various researchers focused their efforts on the synthesis of new dyes for these fibers [7][8][9][10][11][12]. The success of dyeing synthetic textiles, particularly polyester [13][14][15][16][17][18][19][20][21][22][23], with disperse dyes in scCO2 prompted research application of this technique to other synthetic fibers such as polypropylene [24], and aramid fibers [25] or alternative natural fabrics like cotton [26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…Supercritical CO 2 are that it is inexpensive, non-toxic and non-flammable, it can be recycled and it has easily accessible critical conditions by giving an option avoiding water discharge. This new cleaner waterless dyeing technology appears to be economically attractive for the textile industry [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%